If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11-2(y-4)=5(y+1)
We move all terms to the left:
11-2(y-4)-(5(y+1))=0
We multiply parentheses
-2y-(5(y+1))+8+11=0
We calculate terms in parentheses: -(5(y+1)), so:We add all the numbers together, and all the variables
5(y+1)
We multiply parentheses
5y+5
Back to the equation:
-(5y+5)
-2y-(5y+5)+19=0
We get rid of parentheses
-2y-5y-5+19=0
We add all the numbers together, and all the variables
-7y+14=0
We move all terms containing y to the left, all other terms to the right
-7y=-14
y=-14/-7
y=+2
| 7k+3=6k=15k+3=15 | | 7k+3=6k=15 | | 8-5n/2=-2 | | 4m+13=3m+15 | | 15x-6=3x+18 | | 2x+2x=198 | | a*3=215 | | 16.1=7x | | b÷7=-11 | | -2×-9=-2x- | | 35-u=45 | | (5/x-2)-(3/x+2)=(12/^2-4) | | x/5+3x/2=17 | | 3x+4÷x-2=5/6 | | -31=-7x+4(x-7) | | 4v²=-12v-5 | | 2r(3r-2)=0 | | 2500=3x+x | | 14(m+3)-5(3m+6)=44 | | 4/3x-1/2=3/2x+2/3 | | 1/10^40=((1/10^8)+x)(x) | | --a/5=3 | | 10^2+10^-5=x | | 25m+27=77 | | 10n/4=20 | | 10E32=(10E8+x)(x) | | 7m-9=47 | | 10^-40=(10^-8+x)(x) | | X=2y-60 | | 2(u-47)=74 | | 3x-5+2x+3=5x-9 | | 12x−12=12x−12 |